Two species of Rhizoecus Kunckel d'Herculais (Homoptera: Coccoidea: Pseudococcidae) new for the Italian fauna (Bollettino di zoologia agraria e bachicoltura, 2024)
Two species belonging to genus Rhizoecus Kunckel d'Herculais (Homoptera Coccoidea Pseudococcidae) collected on ornamental plants in greenhouses are reported as new for the Italian fauna on ornamental plants. R. dianthi Green, a polyphagous species, was collected on roots of African violets, while R. latus (Hambleton) was collected on roots of Ficus benjamina. For each species brief data on morphology, taxonomy and geographical distribution are given. A key for the identification of the Italian Rhizoecus is also given.
Keywords: ornamental plants; mealybugs; Italia